Faktor-Faktor Fundamental yang Mempengaruhi Harga Saham (Study Empiris pada Perusahaan Manufaktur) - Azizah; Hilda Kumala Wulandari; Anisa Sains Kharisma; Indah Dewi Mulyani; Nur Afridah (Journal of Accounting and Finance (JACFIN), 2019)
This study was conducted to determine and analyze the level of influence of Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS) and Return On Equity (ROE) on stock prices in manufacturing companies that were flattened on the IDX for the 2016-2018 period. The population contained in this study is the financial statements of manufacturing companies that are flattened on the IDX for the 2016-2018 period. The selection of samples used in the study was purposive sampling with predetermined criteria in accordance with the purpose of the study, so that there were 17 samples using the IBM SPSS program. The results of this study explain that: CR has a significant influence on stock prices, DER partially does not have a significant influence on stock prices, EPS partially has a significant influence on stock prices, ROE partially has a significant influence on stock prices partially, CR, DER, EPS and ROE simultaneously have a significant influence on stock prices